Irving Howe : socialist, critic, Jew - Alexander, Edward, 1936- (Indiana University Press, 1998)
For over fifty years, from the 1940s to the 1990s, Irving Howe was a commanding, if controversial, figure in American intellectual life. Writing with the productivity of a major industry, Howe took on issues ranging from left-wing politics and American writers to Yiddish literature, the State of Israel, the condition of the American academy, and New York cultural and literary life. Best known for his prize-winning history of American Jewish immigrant culture, World of Our Fathers, Howe was an outspoken socialist as well as founder and editor of the democratic socialist magazine Dissent. Through a clear, eloquent, and forcefully argued study of Howe's politics, writings, and thought, Edward Alexander constructs a sympathetic yet critical intellectual biography of this complex individual.
Keywords: Howe, Irving.; Howe, Irving; Jews -- New York (State) -- New York -- Biography.; Critics -- New York (State) -- New York -- Biography.; Jewish radicals -- New York (State) -- New York -- Biography.; Jews -- New York (State) -- New York -- Intellectual life.; New York (N.Y.) -- Biography.; New York (N.Y.) -- Intellectual life.; Juifs -- New York (État) -- New York -- Biographies.; Critiques -- New York (État) -- New York -- Biographies.; Radicaux juifs -- New York (État) -- New York -- Biographies.; Juifs -- New York (État) -- New York -- Vie intellectuelle.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- State & Local.; HISTORY -- State & Local -- General.; Critics; Intellectual life; Jewish radicals; Jews; Jews -- Intellectual life; New York (State) -- New York; Verenigde Staten.; United States Local History.; Regions & Countries - Americas.; History & Archaeology.; Biographies; Biografieën (vorm)